The Effect Of Jicama (Pachyrhizus Erosus) Flour Substitution On Sponge Cake Quality - Resya Ramadhani Faizal; Wirnelis Syarif (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
The main background of this research comes from the lack of variation in the utilization of yam flour, which is a food product from the city of Padang, West Sumatra, especially in food products. Here, yam flour acts as a substitute for wheat flour, which is often used in making sponge cake. This study aims to find out the differences in the effects resulting from yam flour substitution, respectively 0%, 25%, 50%, and 75%, on the quality of the shape, color, aroma, texture, and taste of the resulting sponge cake. The experimental design used in this study was a completely randomized design (CRD). The type of data used is primary data obtained using the organoleptic test method, which was carried out on five expert panelists. Data analysis was carried out using ANOVA. In cases where a significant effect is found in the sample, the analysis will be continued using Duncan's test. The results indicated that sponge cake was affected by yam flour substitution, especially on the quality of color (surface and bottom), aroma (jicama), texture (soft and porous), and taste (jima). Meanwhile, no significant effect was found on the shape quality (tidy, according to the mold) of the sponge cake. The best research results were found in the use of yam flour, as much as 75% (X3) in the quality of the shape, color, aroma, texture, and taste of the resulting sponge cake.